Use of a multicomponent, recombinant, meningococcal serogroup B vaccine (4CMenB) for bacterial meningitis prevention. (April 2014) - Esposito, Susanna; Castellazzi, Luca; Bosco, Annalisa; Musio, Alessandra; Stoddard, Jeffrey
Developing effective vaccines against Neisseria meningitidis serogroup B has been challenging for several reasons, including the fact that the capsular polysaccharide of N. meningitidis serogroup B is a poor antigen. Therefore, studies have focused on developing vaccines that target capsular protein meningococcal antigens using reverse vaccinology, a technique that predicts likely vaccine candidates using computational analysis of the whole bacterial genome. This has resulted in a multicomponent, recombinant, meningococcal serogroup B vaccine: 4CMenB (Bexsero ®, Novartis Vaccines & Diagnostics, NC, USA), containing four main immunogenic components: two recombinant fusion proteins ( Neisseria heparin-binding antigen-GNA1030 and factor H-binding protein-GNA2091); recombinant Neisserial adhesion A; and detergent-treated outer membrane vesicles derived from the meningococcal NZ98/254 strain, where porin A 1.4 is the major immunodominant antigen. In this article, we summarize the available clinical data on 4CMenB in healthy infants, adolescents and adults, and discuss the methods available for assessing vaccine efficacy.